PENGARUH KONTRIBUSI SUMBER-SUMBER PENDAPATAN ASLI DAERAH TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH - Kirany, Dhea Satya; Widarno, Bambang (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the influence of the contribution of Regional Original Revenue (PAD) sources on the level of regional financial independence in Regencies/Cities in Central Java Province during the 2019-2023 period. The data used in this study is secondary data. The methods used in this study are descriptive analysis, multiple linear regression analysis, and hypothesis testing by collecting from various sources related to PAD and regional financial independence. The results of the study show that the contribution of regional taxes has a significant positive effect on the level of regional financial independence, the contribution of regional levies has a significant positive effect on the level of regional financial independence, the contribution of the results of segregated regional wealth management has a significant positive effect on the level of regional financial independence, the contribution of other legitimate regional original revenues has a significant positive effect on the level of regional financial independence